2014
DOI: 10.5897/jmpr2014.5689
|View full text |Cite
|
Sign up to set email alerts
|

Influence of arbuscular mycorrhizal fungi on growth, mineral composition and production of essential oil in Mentha × piperita L. var. citrata (Ehrh.) Briq. under two phosphorus levels

Abstract: The aim of the study was to evaluate the effect of the arbuscular mycorrhizal fungi (AMF), Acaulospora morrowiae, Rhizophagus clarus and Scutellospora calospora on the growth and essential oil production of Mentha × piperita L. var. citrata plants. The experiment was conducted in a greenhouse with a 5 × 2 factorial design with five mycorrhizal treatments (uninoculated control, Acaulospora morrowiae, Rhizophagus clarus and Scutellospora calospora, and mixture of inocula) and two P levels (60 and 120 mg P dm -3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…These latter plants did not show any trace of arbuscules, suggesting limited exchanges between the two partners. Many studies report that a high P concentration in the culture medium inhibits the ability of the fungus to establish an efficient symbiosis with plant roots [72][73][74]. Moreover, as confirmed by the PCA, M32 and M96 plants (Figure 4, blue circle) were positively associated to mycorrhizal parameters and were well separated by the M288 plants (that clustered with C288 ones; Figure 4, green circle).…”
Section: Mycorrhization and Plant Growth Parametersmentioning
confidence: 68%
“…These latter plants did not show any trace of arbuscules, suggesting limited exchanges between the two partners. Many studies report that a high P concentration in the culture medium inhibits the ability of the fungus to establish an efficient symbiosis with plant roots [72][73][74]. Moreover, as confirmed by the PCA, M32 and M96 plants (Figure 4, blue circle) were positively associated to mycorrhizal parameters and were well separated by the M288 plants (that clustered with C288 ones; Figure 4, green circle).…”
Section: Mycorrhization and Plant Growth Parametersmentioning
confidence: 68%
“…No increment in essential oil and menthol content occurs at high P level. An enhancement of secondary metabolite production in Mentha piperita L. (peppermint) plants, inoculated with AMF in relation to nutrient availability and uptake, was reported also by Silva et al (2014) and by Arango et al (2012).…”
Section: 9mentioning
confidence: 88%
“…A number of studies demonstrate that the associations of PGPR and AMF with aromatic and officinal plants positively affect the quantitative and/or qualitative profile of the secondary metabolites (e.g., essential oils and alkaloids), in addition to improved growth parameters, biomass and yield (Khaosaad et al 2006;Copetta et al 2007;Banchio et al 2008;Arango et al 2012;Roshanpour et al 2014;Silva et al 2014).…”
Section: 9mentioning
confidence: 99%
“…Mycorrhizal fungi can enhance water uptake through improvement of the root hydraulic conductivity through a larger surface area of the mycelium [28]. The symbiotic association between plant roots and fungi increases access to nutrients, especially those with low mobility, such as phosphorus, zinc and copper, over time [28][29][30]. More-over, it was reported that the inoculation of mycorrhizal fungi with host plants improves plant tolerance in the face of biotic and abiotic stresses through increasing the activity of antioxidant enzymes, reducing chlorophyll decomposition rate and promoting chlorophyll synthesis [31,32].…”
Section: Introductionmentioning
confidence: 99%